INFLUENCE OF CACTUS MUCILAGE AND BROWN SEAWEED EXTRACT ON THE DEGREE OF HYDRATION OF ORDINARY PORTLAND CEMENT PASTES (Nexo Revista Científica, 2018)
This paper presents the effect produced by the addition of aqueous dispersions of cactus mucilage and brown seaweed extract on the degree of hydration of ordinary Portland cement pastes. Cement pastes with water/cement ratios of 0.30 and 0.60 were prepared containing the natural additives at three concentrations. The curing conditions were moist cured and sealed. The degree of hydration was determined by ignition and thermo-gravimetric analysis at 14, 28 and 56 days of age. The results indicate a higher degree of hydration in pastes with a water/cement ratio of 0.60 containing the natural additives with respect to control specimens. This effect could be explained by a better dispersion of cement particles in the presence of the natural additives and their capacity to retain water, thereby providing internal curing.